Integrative and Conjugative Elements of Helicobacter pylori Are Hypothetical Virulence Factors Associated With Gastric Cancer - Mucito-Varela, Eduardo; Castillo-Rojas, Gonzalo; Calva, Juan J.; López-Vidal, Yolanda (Frontiers in Cellular and Infection Microbiology, 2020)
Helicobacter pylori is associated to diverse gastric pathologies among which gastric cancer (GC) represents a global health threat due to a high mortality rate. Several virulence factors have been identified but remain insufficient to accurately predict the risk of H. pylori-associated GC. In order to identify potentially helpful disease biomarkers, we compared 38 complete genomes and 108 draft genomes of H. pylori isolated worldwide from patients with diverse gastric pathologies and 53 draft genomes of H. pylori isolated from Mexican patients with GC, intestinal metaplasia, gastritis, peptic ulcer, and dyspepsia. We tested the cytopathic effects on AGS cells of selected H. pylori strains with known cag-PAI and ICE status (H. pylori strains 29CaP, 29CaCe, 62A9, 7C, 8822 and 26695) and the histopathological damage of H. pylori 29CaP and 62A9 in a mouse model. H. pylori isolated from GC patients were 3 to 11 times more likely to harbor any of seven genes encoded within an integrative and conjugative element (ICE) than H. pylori isolated from subjects with other gastric pathologies. H. pylori 29CaP, which harbors a complete ICEHptfs3 but lacks cag-PAI, elicited a strong cytopathic effect and higher histopathological scores compared to other H. pylori strains carrying cag-PAI and hybrid ICE with incomplete TFSS. The presence of functional ICE region is a high risk factor to develop gastric cancer.